Pelatihan Teknis dan Etika Petugas Upacara Bendera Dalam Memperingati HUT RI Sebagai Wujud Pendidikan Karakter - Anwar, Saiful; Abdullah, Abdullah; Subahannor, Subahannor (CV. Era Digital Nusantara, 2025)
This study aims to describe the process of mentoring technical and ethical training for flag ceremony officers in commemorating the Indonesian Independence Day in schools through a Service Learning approach that includes the stages of investigation, preparation, implementation, and reflection. The activity begins with student identification and needs analysis, training in theory and protocol norms, implementation of technical and ethical exercises, followed by reflection at the end of the activity. The results of the study indicate that this method is effective in improving the technical skills of ceremony officers, such as marching, flag raising, and teamwork, as well as instilling the values ​​of discipline, responsibility, nationalism, and morality. This mentoring model not only significantly improves the skills and character of students but also creates an interactive and meaningful learning atmosphere. Overall, the Service Learning approach in this training successfully strengthens character formation and love for the homeland through effective and meaningful flag ceremony activities.